2015
DOI: 10.5539/ies.v9n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Learning Assessment Practices Used by Jordanian Teachers of Mathematics for Grades (1-6)

Abstract: <p class="apa">This study aims to investigate the students’ learning assessment practices used by Jordanian teachers of mathematics for grades (1-6) in Amman. The sample of the study consists of (402) teachers. A questionnaire of (72) items are developed on four domains, namely: questions, homework, exams, and alternative strategies. Validity and reliability are established. Results of the study show that the mean of the scores for the four domains and the entire items are medium, the highest was on exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The instrument used in this research was the APMT scale, which is a self-reported questionnaire that consists of 5-point Likert scale items as (1: Never; 2: Rarely; 3: Sometimes; 4: Mostly; 5: Always). The development of the scale in started by analysing a few scales of teachers' assessment practice that have been established in previous studies such as Abed and Awwad (2016), Alkharusi et al (2012) and Genc (2005). Then, the items were checked if they can be used to measure teachers' assessment practices of mathematical thinking.…”
Section: Methodology Research Design and Instrumentmentioning
confidence: 99%
See 4 more Smart Citations
“…The instrument used in this research was the APMT scale, which is a self-reported questionnaire that consists of 5-point Likert scale items as (1: Never; 2: Rarely; 3: Sometimes; 4: Mostly; 5: Always). The development of the scale in started by analysing a few scales of teachers' assessment practice that have been established in previous studies such as Abed and Awwad (2016), Alkharusi et al (2012) and Genc (2005). Then, the items were checked if they can be used to measure teachers' assessment practices of mathematical thinking.…”
Section: Methodology Research Design and Instrumentmentioning
confidence: 99%
“…Several studies around the world have examined teachers' assessment practices from different aspects. For instance, Abed and Awwad (2016), Genc (2005), and Wallace and White (2014) investigated mathematics teachers' assessment practices as a part of their teaching practices. They have studied the assessment of teaching and assessment of learning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations